A Test of Riskâ€“Return Relationship for Stocks Traded on the NSE - Lalitha, N. (Indian Journal of Research in Capital Markets, 2025)
Purpose : The beta of a stock captures the market risk associated with that stock, and investors construct portfolios using stocks with different levels of beta to get the desired level of risk. The CAPM model helped identify underpriced and overpriced assets using beta to estimate their expected return. Understanding the role of beta in determining average returns on portfolios is, therefore, of great importance. This paper tested the significance of beta and a non-beta measure of risk in explaining average returns on portfolios constructed from stocks traded on the National Stock Exchange. Methodology : The study covered the period from January 2006 to December 2023. Rolling regression was done to get robust estimates of portfolio-level variables. Econometric software GRETL was used to run OLS regressions to examine whether portfolios with higher â€œbetaâ€ had higher expected returns. Findings : The study did not find a statistically significant positive riskâ€“return relationship, possibly due to non-normality in portfolio returns for a significant period of the study. Further, the coefficient of beta was found to be negative for the period from 2014â€“2018. Practical Implications : Since beta was estimated from past data, it should be used alongside other factors to estimate expected returns from assets. Incorporating biases in investorsâ€™ behavior was a possible way forward for a better understanding of the market. Originality : This study was based on stocks traded on the NSE and covered a period that witnessed a currency withdrawal, a pandemic, and many technological innovations and regulatory reforms in the capital market.